Peningkatan Hasil Belajar Matematika melalui Penerapan Metode Problem Based Learning Masa Pandemi Covid-19 pada Siswa Kelas IX-1 SMP Negeri 1 Masbagik Semester Ganjil - Pujawati, Baiq Sri (Lembaga Yasin AlSys, 2021)
The purpose of this classroom action research (CAR) is to find out the extent to which students' learning outcomes in Mathematics are improved by applying the Problem-Based Learning Method. In this classroom action research (CAR), it is carried out in 2 cycles, from the results of the actions taken it is proven to be able to improve student learning outcomes by achieving the classical mastery that is set at 85%. Classical completeness 62.5% obtained in the first cycle, can be increased in the second cycle to 85.4%. In terms of student activity, there was also an increase, namely in the first cycle, the moderately active category increased to an active category. The results of this action research indicate that the application of the Problem-Based Learning Method can improve student learning outcomes in Mathematics with completeness reaching 100%.